Subungual Bowen’s Disease: Clinical Mimicker of Subungual Melanoma - Ritu Rani; Reena Kumari Sharma; Mudita Gupta (Clinical Dermatology Review)
Bowen’s disease (BD) is a benign epidermal premalignant tumor histopathologically characterized by the presence of dysplastic cells limited to the epidermis. Subungual BD is a less commonly described entity and involvement of toenails is even rarer probably because of less cosmetic concern, especially in elderly males. As clinical characteristics of subungual BD are not clearly defined, creating diagnostic dilemma with various benign and malignant diseases such as fungal infections with nail pigmentation and subungual melanoma, respectively. The patient is often misdiagnosed to be having benign and malignant diseases such as fungal infections and warts, leading to delay in diagnosis. We report a case of subungual BD simulating melanoma in a 75-year-old male.